Plasma ddPCR for etiological diagnosis of focal bacterial infections - Zhang, Yongfeng; Weng, ShanShan; Ma, Xueqing; Lin, Ling; Chen, Yueliang; Feng, Binbin; Xia, Jiang; Ye, Jiayuan; Zhou, Hua; Yu, Yunsong; Zhao, Dongdong (Frontiers in Medicine, 2025)
BackgroundPlasma droplet digital polymerase chain reaction (ddPCR) has been used for pathogen detection and has shown good diagnostic value, but no studies have yet demonstrated its application in focal infections. Herein a pilot study using plasma ddPCR to diagnose focal infection is discussed.MethodsEight patients with a diagnosed focal infection who underwent plasma ddPCR for bacterial detection between 2021 and 2022 in Sir Run Run Shaw hospital were enrolled in this retrospective single-center pilot study. Results of ddPCR and focal cultures were compared as well as the turnaround time of two methods and other clinical data.ResultsIn 7/8 cases, plasma ddPCR results were consistent with focal culture results. The turnaround time for ddPCR was 2.5 h, significantly lower than the average time for focal cultures of 2.63 days.ConclusionThis pilot study indicates the promising value of the plasma ddPCR method in the rapid diagnosis of focal infection. If larger studies support the findings here, this method can help improve diagnostic accuracy and guide treatment decisions in suspected focal infections.